Pengembangan Video Pembelajaran Tari Indang pada Mupel SBdP Kelas VI di Sekolah Dasar - Nana Prasetya Ayuni; Wawan Priyanto; Mei Fita Asri Untari (STKIP Andi Matappa Pangkep, 2022)
The background of the research is the lack of interest of students in learning the art of dance, the limited expertise of teachers and the lack of school facilities. The main object of this research is to determine the characteristics, validity, and practical elements of developing video learning by using